2014
DOI: 10.1128/jb.01978-14
|View full text |Cite
|
Sign up to set email alerts
|

cbb 3 -Type Cytochrome c Oxidases, Aerobic Respiratory Enzymes, Impact the Anaerobic Life of Pseudomonas aeruginosa PAO1

Abstract: For bacteria, many studies have focused on the role of respiratory enzymes in energy conservation; however, their effect on cell behavior is poorly understood. Pseudomonas aeruginosa can perform both aerobic respiration and denitrification. Previous studies demonstrated that cbb 3 -type cytochrome c oxidases that support aerobic respiration are more highly expressed in P. aeruginosa under anoxic conditions than are other aerobic respiratory enzymes. However, little is known about their role under such conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 37 publications
3
23
0
Order By: Relevance
“…As shown by Yoon and coworkers and confirmed in a more recent study (64,65), P. aeruginosa PAO1 cells grown anaerobically are more elongated than that grown aerobically and easily form highly cohesive clumps, yielding a robust biofilm. Cell elongation is dependent on the presence of NIR and is repressed in the presence of an NO antagonist.…”
Section: Endogenous Sources Of No In P Aeruginosa and Their Effects supporting
confidence: 53%
“…As shown by Yoon and coworkers and confirmed in a more recent study (64,65), P. aeruginosa PAO1 cells grown anaerobically are more elongated than that grown aerobically and easily form highly cohesive clumps, yielding a robust biofilm. Cell elongation is dependent on the presence of NIR and is repressed in the presence of an NO antagonist.…”
Section: Endogenous Sources Of No In P Aeruginosa and Their Effects supporting
confidence: 53%
“…In contrast, the ANR-independent one is constitutively expressed and not directly dependent on oxygen concentrations ( 8 , 39 ). Recently, Hamada and coworkers showed that the P. aeruginosa cbb 3 -C c Os accumulate nitric oxide and are involved in biofilm formation during the anaerobic denitrification process ( 40 ). In addition, cbb 3 -C c Os were reported to be expressed under anaerobic conditions in several other bacterial species, e.g., Shewanella oneidensis , Bradyrhizobium japonicum , and Rhodobacter capsulatus ( 19 , 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…24) In addition, it was recently demonstrated that a respiratory enzyme affects biofilm formation, indicating roles other than energy conservation in the formation of a multicellular community under certain conditions. 25) In Clostridium perfringens, a gram-positive, spore-forming, anaerobic pathogen, temperature changes drastically affect biofilm morphology, including thickness and cell density, reflecting the temperature-dependent regulation of EPS production (Fig. 2).…”
Section: Surface Attachmentmentioning
confidence: 99%